Selection and characterization of probiotic lactic acid bacteria with heterocyclic amine binding and nitrosamine degradation properties - Yodsawee Duangjitcharoen, Duangporn Kantachote, Chutinun Prasitpuripreecha, Sartjeen Peerajan, Chaiyavat Chaiyasut (Journal of Applied Pharmaceutical Science, 2014)
Potential probiotic strain for being health protectant especially intestinal illness is strain specific. This study investigated the selection of a new strain of probiotic of non-human origin and of human origin with the properties of intestinal protection against cancer. From the primary screening results, the human feces origin strains showed more bile salt tolerance than the fermented food origin strains. Whereas none of the human feces origin isolates could grow well in the acid condition. Lactobacillus plantarum CM4 was the new probiotic of non-human origin strain for this study. CM4 cells is said to tolerate and grow in 0.3% bile salt after 5 hours of incubation, at pH3 after 6 hours of incubation. This is in agreement with in vivo study for intestinal adherence ability of probiotic, a live CM4 cells was able to persist in mice small intestine and colon for 5 days. Live CM4 cells showed most effectiveness to bind 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) mutagen after 24 hours of incubation with 46.32% of binding ability while 144 hours of incubation with 85.34% of binding ability was the most effective for 2-amino-3-methylimidazo[4,5-f]quinoline (IQ) mutagen. The significant difference (p
Keywords: Probiotic, Lactobacillus plantarum, heterocyclic amine, nitrosamine, cancer.